Performance Analysis of the Legislative Body of the House of Representatives of the Republic of Indonesia during the Covid-19 Pandemic 2020 – 2021 - I Gede Ria Mahendra; Azhari Aziz Samudra; Evi Satispi; Retnowati WD Tuti (Syntax Corporation, 2023)
The process of harmonization and strengthening of the draft bill is the most crucial stage in the formation of legislation. The 2019 Corona Virus Disease pandemic in Indonesia caused a socio-economic crisis. Among the challenges is the delay in the Legislative Body's big agenda in drafting laws. This study uses a qualitative method with a descriptive analysis approach. The theory used is the Balanced Scorecard Organizational Performance, with 4 perspectives: Finance, Customer, Internal Business, Learning and Growth. The results of the study describe that the performance of the Legislative Body is related to the Financial Perspective, experiencing refocusing and budget reallocation to overcome the Corona Virus-2019. From the customer perspective, in absorbing the aspirations of the community, the legislative body can only conduct public hearings, seminars, and work visits with using virtual under the rules of the DPR RI. From an Internal Business perspective, the implementation is still not optimal, because it is constrained by the Legislation Board meeting schedule with the commission meeting schedule, and attending meetings online. Furthermore, in the Learning and Growth Perspective, the leadership in the Legislative Institution is quite optimal, seen from the commitment and presence of the leadership of the Legislative Institution in carrying out their duties. The absence of laws that have been ratified, is mostly due to the political process in the formation of laws that cannot be measured quantitatively.